Can FESS Combined with Submucosal Resection (SMR)/Septoplasty Reduce Revision Rate?. (October 2014) - Chang, Chan-Chi; Tai, Chih-Jaan; Ng, Teik-Ying; Tsou, Yung-An; Tsai, Ming-Hsui
Objectives: Our study was designed to ascertain the outcomes of functional endoscopic sinus surgery (FESS) combined with submucosal resection (SMR)/septoplasty in reducing FESS revision rates. Study Design: Retrospective population-based study. Setting: Academic tertiary medical center. Subjects and Methods: By using the Taiwan Longitudinal Health Insurance Database, we obtained the patients who underwent FESS for chronic rhinosinusitis. These patients were divided into 2 groups: the control group (FESS alone) and the study group (FESS combined with SMR). The primary outcome was the revision operative rate. Results: In total, 4484 patients who had undergone FESS were recruited into this study. The number of patients who underwent revision FESS was 528 (11.78%). In our sample, 80.45% of patients received FESS alone, whereas 19.54% of the patients underwent concurrent SMR/septoplasty during FESS. There are more female patients and older patients in the control group than in the study group. The revision rates of these 2 groups were significantly different (12.36% vs 9.36%, respectively; P = .016). Moreover, logistic regression analysis came out that patients in the control group had a higher revision rates than those in the study group. Male patients and younger patients were found to have higher revision rates. In addition, patients with asthma or allergic rhinitis had higher revision rates compared with those patients without these 2 comorbidities. Conclusions: This study showed an association between FESS combined with concurrent SMR/septoplasty and less incidence of revision rate of FESS. Patients with asthma or allergic rhinitis have an increased risk of requiring more revision surgeries after FESS.